Conservative Management of Invasive Placentation: Two Cases with Different Surgical Approaches - Emily E. Fay; Barbara Norquist; Jennifer Jolley; Melissa Hardesty (Thieme Medical Publishers, Inc., 2016)
Abstract Background When placenta accreta complicates a delivery, the typical management is to perform a cesarean hysterectomy. Other management strategies, including leaving the placenta in situ, have been attempted and supported in some cases. This may allow for an interval hysterectomy, which can potentially decrease average blood loss and/or allow a minimally invasive approach to the hysterectomy. Cases We present two cases of women with invasive placentation managed conservatively with interval hysterectomy. One woman was managed with robotic-assisted laparoscopic surgery and the other with an open surgical approach. Conclusion These cases highlight the successful use of conservative management for invasive placentation in two stable patients and showcase the novel use of a robotic-assisted laparoscopic surgery for management of invasive placentation.